Penerapan Model Game Connecting Sentence Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas 5 SDN 4 Limboto - Domut, Ikmawati; Pateda, Lamsike; Talango, Sitti Rahmawati (Al-Azkiya: Jurnal Pendidikan MI/SD, 2024)
This reseach aims to determni the implementation on the game-based learning model connecting sentence to improve student's learning outcomes in the Indonesian language subject with the theme Our Friends Environment For Grade V at SD Negeri 4 Limboto. This kind of research, known as classroom action research, seeks to describe the conclusions the reasearcher made thite conducting filedwork. Data collection techniques were carried out through interview/observations, test and documentation. The results of this studi indicate that at significant increase proves that the application of the connecting sentence game leaning model using sentence card media to improve student learning outcomes in the pre-cycle, witch is 50%, cycle 1 meeting 1 the percentage of student learning outcomes increased to 54%, cycle 1 meeting 2 the percentage increased to 66% and in cycle 2 the student learning outcomes increased to 100%. So that the percentage of learning outcomes obtained by student are more focused and active in the learning process, as well as teachers explaining the leasson material briefly but crearly so that it can be understood by student. Thus, the learning process runs well.